A Theoretical Model for Predicting the Ultimate Strength of Superalloys in a Wide Temperature Range. Issue 10 (13th April 2022) - He, Yi; Li, Weiguo; Yang, Mengqing; Zhao, Ziyuan; Dong, Pan; Ma, Yanli
Abstract : Nickel‐based superalloys are often serviced as high‐temperature‐resistant materials. Strength prediction at elevated temperatures is the fundamental issue of equipment performance evaluation in service environment. Herein, the quantitative effect of temperature on the ultimate tensile strength (UTS) of nickel‐based superalloys is investigated. A theoretical model for predicting the temperature‐dependent UTS of nickel‐based superalloys is developed from an energy equivalence perspective. A quantitative relationship is established between UTS and temperature. The model can predict the UTS at different temperatures only using the tensile test data at room temperature and the melting point temperature of the material. Theoretical predictions agree well with nine nickel‐based superalloys experimental data over a wide temperature range. In addition, iron‐based and cobalt‐based superalloys are verified using the proposed model. The significance and applicability scope of the model is also discussed. Research results provide a new alternative approach for predicting the temperature‐dependent UTS of superalloys under service conditions. Abstract : Superalloys are often used as high‐temperature‐resistant materials. It is essential to obtain their mechanical properties at different temperatures for the safety and reliability of the equipment. Herein, a theoretical model is proposed to predict the ultimate strength of superalloys at different temperatures. The model is validated by experimental data.